AN ANALYSIS OF TYPES OF ADVERBIAL CLAUSE IN MOVIE ALICE IN WONDERLAND - Febriany, Mariaty; Handayani, Nurma Dhona (IdeBahasa, 2024)
This descriptive qualitative research aimed to investigate the types of adverbial clauses in the movie "Alice in Wonderland". The study focused on the dialogue and subtitles of the film. The researchers selected utterances containing adverbial clauses as the primary data source. Data collection employed an observational method with a non-participatory technique. The analysis utilized a clause-identifying method and a differentiating comparative technique. The theoretical framework applied was Huddleston and Pullum's (2002) typology of adverbial clauses. The results revealed that adverbial clauses were frequently used in the film's dialogue to add context and complexity to the narrative. From 49 identified instances of adverbial clauses, 31 were categorized as conditional, 9 as time, 2 as comparison and 7 as causal. Conditional clauses emerged as the most common type of adverbial clause used. The characters primarily used these clauses to express hypothetical situations, temporal relationships, and cause-effect connections in a way that enhanced the fantastical and whimsical nature of the story.